VALUABLE ATTITUDE TOWARDS LAW AS A FOUNDATION FOR REALIZATION OF LAW CONCEPTS - Matviichuk, Andrii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Goal: conceptualization of the scientific stance in terms of addressing the phenomena of valuable attitude with the goal of reaching higher effectiveness of law concepts realization within the domestic practice of social relationships. In order to reach the mentioned above aim the concepts of law were analyzed, methodological ways of valuable attitude and the intelligence were characterized, as well as the perspective of the mentioned practice involvement when it comes to formulating the motives and goals of constructing the social reality. Methods used in the paper: analytical, general and systematic in combination with axiological approach. Results: on the theoretical level of the paper it was explained that valuable attitude towards law as well as advanced valuable intelligence are the prerequisites of the well-balanced decision when it comes to legal discourse. Discussion: modern law axiology has formed the holistic system of law concepts, namely justice, freedom, equality, human rights and humanism. Practical realization of the law concepts correlates with the valuable attitude towards law; practical application of law concepts means the advanced valuable intelligence. Valuable attitude is meant to be examined as the aspect of established social values, what comes as a motivation and leads the activity of both individual and society in terms of law concepts affirmation. Moreover, the valuable intelligence manifests itself within either social or professional activity as an ability to be effective in solving conflicts and problems, taking the values and concepts of law into account.